Public Perceptions of the Quality of Public Services at the Sumberduren Village Office, Tarokan District, Kediri Regency - Putri, Dian Nurmala (Universitas Negeri Semarang, 2020)
Public services according to Undang- Undang Nomor 25 Tahun 2009 are a series of activities in meeting service needs in accordance with laws and regulations for every citizen and resident of goods, services, and/or administrative services provided by public service providers. Public services are things that must be carried out by the government to fulfill the rights of citizens. In the opening Undang- Undnag Dasar 1945, which in it mandates that one of the objectives of the Republic of Indonesia is to promote general walfare and educate the nation’s life. The legal basis for public services in Indonesia is Law Number 25 of 2009. Public perception is the process of community assessment of certain objects. This study aims to determine the public’s perception of the quality of public services at the Sumberduren Village Office, Tarokan District, Kediri Regency. The data used in this study is primary data obtained directly from the object of research through direct interviews with respondents, while secondary data uses books and scientific journal writings. Based on the result of the study, it can be concluded that the public’s perception of the quality of public services at the Sumberduren Village Office, Tarokan District, Kediri Regency is optimal enough in providing services to the community.